Geochemistry of biotite from Kuala Lumpur Granite - A. Ghani, Azman (Malaysian Journal of Science (MJS), 2002)
This work presents a new biotite analyses of Kuala Lumpur granite. The biotites have been analysed from three different samples namely equigranular normal biotite-muscovite granite (NBMG), deformed muscovite granite (DBMG) and porphyritic biotite-muscovite granite (PBMG). Geochemistry of the biotite is similar to the biotite crystallised from peraluminious melt, characterised by high Al_20_3. The compositions of the biotite under study were defined by F0_2 near to that of the Si0_2-Fe_2SiO_4-Fe_30_4 buffer.